Microglia Phenotypes Converge in Aging and Neurodegenerative Disease - Candlish, Michael; Hefendehl, Jasmin K. (Frontiers in Neurology, 2021)
Microglia, the primary immune cells of the central nervous system, hold a multitude of tasks in order to ensure brain homeostasis and are one of the best predictors of biological age on a cellular level. We and others have shown that these long-lived cells undergo an aging process which impedes their ability to perform some of the most vital homeostatic functions such as immune surveillance, acute injury response and clearance of debris. These time-induced cellular alterations lead to microglial aging which can worsen overall disease outcomes and furthermore can represent a pathomechanistic step towards neurodegeneration in itself. Microglia have been described as gradually transitioning from a homeostatic/resting state to an activated state in response to various insults including aging. However, microglia show diverse and distinct responses to presented stimuli in the form of acute injury or chronic disease. This complexity is further compounded by the distinct alterations that globally occur in the aging process. In this review, we examine the differences and similarities between different microglia states and dissect the transcriptomic and pathological alterations that occur in microglial aging; potentially leading to the development and exacerbation of neurodegenerative disease.